Fundamentals of Entrepreneurship (ENT 300) : Chacha cake house / Mohamad Nadeem Arbi … [et al.] - Arbi, Mohamad Nadeem; Arifin, Rafiq Syahmi; Rakawi, Danial Fitri; Abang Mohamad, Abang Hamizan (2018)
Chacha Cake House begins since 2018. Chacha first branch first set it footprint on Jalan Kota Samarahan which is a small outlet. Chacha is one of the most popular outlet in town in delivering the best quality products to the customers in town. Chacha Cake House serve all range of products from plain bread to French croissants, traditional layer cakes to popular western cheese cake. Furthermore, the branches of this outlet will start its operation hour from 10am until 9pm depending on the branch operating area. This Chacha Cake House is the most popular and top among the other bakery shop.